Pengaruh nilai tukar dan ekspor terhadap harga saham perbankan sebelum dan setelah pengumuman covid-19 - Tampubolon, Vienna Agatha; Ibnu Abbas, Muhammad Hasyim (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Covid-19 hampered most businesses and caused a banking crisis that triggered uncertainty so that economic growth declined. Banks can dampen these economic shocks by providing much-needed funding for companies, especially those affected by Covid-19. The bank can obtain these funds by selling stocks to the public. However, some factors affect stock prices, such as exchange rates, exports, and unexpected conditions such as Covid-19. Based on existing research, stock prices in general after Covid-19 have fallen drastically. Therefore, it is hoped that this research can help the Indonesian government control exchange rates and exports so that the price of banking stocks does not experience a drastic decline when unexpected situations such as Covid-19 occur. This study uses a panel data analysis technique. The results of this study are that the exchange rate and exports have a significant effect on stock prices, but conditions before and after Covid-19 have no significant effect on stock prices. It is expected that investors and the government can consider the factors that affect stock prices.